Vitamin E inhibits IL-4 gene expression in peripheral blood T cells - Li-Weber, Min; Krammer, Peter H. (European journal of immunology, 2002)
IL-4 plays a pivotal role in the development of allergic inflammation via induction of IgE isotype switching, increase of IgE receptor expression, promoting Th2 cell differentiation, and stimulating several genes involved in atopic disorders. Previous studies in human and mouse models have shown that high vitamin E intake correlates with low IgE concentration and reduced prevalence of allergic reactions. We, therefore, investigated the mechanism of the vitamin E effect on T cells. We show here that the natural free radical scavenger vitamin E suppresses IL-4 protein levels in humanperipheral blood T cells in a dose-dependent manner. The effect of vitamin E on IL-4 expression occurs at the mRNA level. Vitamin E has been implicated in inhibition of DNA binding and function of the redox-regulated transcription factors NF-κB and AP-1. Investigation of the molecular mechanism by which vitamin E suppresses IL-4 transcription shows that it blocks binding of transcription factors to two important IL-4 promoter binding sites for NF-κB and AP-1 and interferes with promoter activity upon T cell activation. Our data provide molecular evidence supporting the beneficial effect of dietary vitamin E on atopic disorders.
Gesehen am 15.04.2021